2024
DOI: 10.1093/jbmrpl/ziae002
|View full text |Cite
|
Sign up to set email alerts
|

Postfracture survival in a population-based study of adults aged ≥66 yr: a call to action at hospital discharge

Geneviève Vincent,
Jonathan D Adachi,
Emil Schemitsch
et al.

Abstract: Post-fracture survival rates provide prognostic information but are rarely reported along with other mortality outcomes in adults aged ≥50 years. The timing of survival change following a fracture also needs to be further elucidated. This population-based, matched-cohort, retrospective database study examined 98 474 patients (73% women) aged ≥66 years with an index fracture occurring at an osteoporotic site (hip, clinical vertebral, proximal non-hip non-vertebral [pNHNV], and distal non-hip non-vertebral [dNHN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In their recent population–based study of nearly 100 000 patients from Ontario, Canada, who had suffered a fracture, Vincent et al. 1 characterized postfracture survival rates. They found that overall survival was decreased following fracture, particularly following fractures of the hip or vertebrae, with the increased mortality risk starting immediately after fracture occurrence.…”
mentioning
confidence: 99%
“…In their recent population–based study of nearly 100 000 patients from Ontario, Canada, who had suffered a fracture, Vincent et al. 1 characterized postfracture survival rates. They found that overall survival was decreased following fracture, particularly following fractures of the hip or vertebrae, with the increased mortality risk starting immediately after fracture occurrence.…”
mentioning
confidence: 99%